Computer aided interactive pressure vessel design - Teoh, Sun Jie (2008)
Designing a pressure vessel using a handbook is troublesome and not interactive. Therefore computer aided software is created to assist the users, however due to business benefit, the computer aided software for designing pressure vessel are not for sale or pricey. This project is to develop an interactive system to design pressure vessels besides the understanding of the algorithm in designing pressure vessel. Results generated by the system were to compare with manual calculations using ASME VIII-1 design code. Beside that, a finite element model was created using the results generated by the system and the maximum stress value in finite element analysis was to compare with theoretical calculation. This project includes comparison studies to compare self defined material with material library, comparison for self defined load with load from substance library and comparison for substance library liquid with substance library gas. Software Microsoft Visual Basic 6.0 is used for the purpose of building the interactive interfaces and processing the data. The system applied formulae from ASME VIII-1 design code and the finite element analysis is using software ALGOR V16. As a conclusion, designing a pressure vessel using computer aided tool is easier and interactive beside low time consumption, therefore, the project Computer Aided Interactive Pressure Vessel Design is able to contribute to the human kind beneficial and should extend the study to become a tool that able to design for all kind of pressure vessel.